2018
DOI: 10.1038/s41419-018-0950-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-495-3p inhibits multidrug resistance by modulating autophagy through GRP78/mTOR axis in gastric cancer

Abstract: Multidrug resistance (MDR) accounts for poor prognosis in gastric cancer (GC). MicroRNAs (miRNAs) are critical regulators of MDR via modulation of the target genes. The present study revealed that miR-495-3p could act via a target gene, GRP78, to regulate the process of autophagy and inhibit MDR. Based on the in vitro and in vivo gain-of-function or loss-of-function experiments, overexpression of miR-495-3p was sufficient to reverse the MDR to four chemotherapeutics in vitro and inhibit the tumor growth in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 35 publications
3
63
1
Order By: Relevance
“…Our previous research showed that GRP78 is overexpressed and correlated with invasion, metastasis and poor prognosis in esophageal squamous cell carcinoma (ESCC) patients [20]. Besides, the expression of GRP78 is shown to be signi cantly higher in multidrug resistance in gastric cancer cells and knockdown of GRP78 signi cantly reversed multidrug resistance in gastric cancer [21][22]. All these studies con rmed that GRP78 is involved in the pathological process of numerous cancers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous research showed that GRP78 is overexpressed and correlated with invasion, metastasis and poor prognosis in esophageal squamous cell carcinoma (ESCC) patients [20]. Besides, the expression of GRP78 is shown to be signi cantly higher in multidrug resistance in gastric cancer cells and knockdown of GRP78 signi cantly reversed multidrug resistance in gastric cancer [21][22]. All these studies con rmed that GRP78 is involved in the pathological process of numerous cancers.…”
Section: Discussionmentioning
confidence: 92%
“…Recent molecular and pathological studies have reported that glucose-regulated protein (GRP78) is involved in tumor development and progression [16][17][18][19][20][21][22]. GRP78 (which is also known as HSPA5) is reported to be involved in ER stress and overexpression of many types of human cancers, such as hepatocellular carcinoma, esophageal cancer, gastric cancer and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence have validated that miRNAs are capable of regulating autophagy via affecting intracellular levels of key molecular proteins involved in the autophagic process . Recent study has demonstrated that miR‐495‐3p could inhibit autophagy in MDR GC cells by activating mTOR signaling and targeting GRP78 . Zhang et al indicated that miRNA‐218 inhibited GC MDR by de‐regulating expression of SMO in the Hedgehog/smoothened pathway .…”
Section: Mirnas and Drug Resistance In Gcmentioning
confidence: 99%
“…169 Recent study has demonstrated that miR-495-3p could inhibit autophagy in MDR GC cells by activating mTOR signaling and targeting GRP78. 170 Zhang et al indicated that miRNA-218 inhibited GC MDR by de-regulating expression of SMO in the Hedgehog/smoothened pathway. 148 Moreover, Li et al validated that miRNA-148a-3p suppressed the cellular-protective autophagy in cisplatin-resistant GC cells by activating mTORC1 activity and inhibiting RAB12 expression.…”
Section: Role Of Mirnas In Signaling Pathways Of Gcmentioning
confidence: 99%
“…In this process, total complementarity results in the cleavage of the mRNA target strand, while imperfect complementarity leads to repression of the mRNA translation [51]. Thus, unsurprisingly, miRNA deregulation has been described in different diseases, including GC [47,52], and this deregulation may help us elucidate critical pathways involved in carcinogenesis processes and identify potential prognostic or predictive biomarkers [53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%